Predicting Early Allograft Function After Normothermic Machine Perfusion. Issue 12 (29th August 2022) - Watson, Christopher J.E.; Gaurav, Rohit; Fear, Corrina; Swift, Lisa; Selves, Linda; Ceresa, Carlo D.L.; Upponi, Sara S.; Brais, Rebecca; Allison, Michael; Macdonald-Wallis, Corrie; Taylor, Rhiannon; Butler, Andrew J.
Abstract : Background: Normothermic ex situ liver perfusion is increasingly used to assess donor livers, but there remains a paucity of evidence regarding criteria upon which to base a viability assessment or criteria predicting early allograft function. Methods: Perfusate variables from livers undergoing normothermic ex situ liver perfusion were analyzed to see which best predicted the Model for Early Allograft Function score. Results: One hundred fifty-four of 203 perfused livers were transplanted following our previously defined criteria. These comprised 84/123 donation after circulatory death livers and 70/80 donation after brain death livers. Multivariable analysis suggested that 2-h alanine transaminase, 2-h lactate, 11 to 29 mmol supplementary bicarbonate in the first 4 h, and peak bile pH were associated with early allograft function as defined by the Model for Early Allograft Function score. Nonanastomotic biliary strictures occurred in 11% of transplants, predominantly affected first- and second-order ducts, despite selection based on bile glucose and pH. Conclusions: This work confirms the importance of perfusate alanine transaminase and lactate at 2-h, as well as the amount of supplementary bicarbonate required to keep the perfusate pH > 7.2, in the assessment of livers undergoing perfusion. It cautions against the use of lactate as a sole indicator of viability and also suggests a role for cholangiocyte function markers in predicting early allograft function. Abstract :